Aprendizagem docente do professor surdo: a produção de saberes sobre a escrita da língua de sinais - Hautrive, Giovana Medianeira Fracari (2016)
This research is part of the research line Formation, Knowledge and Professional Development of the Pos-Doctoral Degree in Education Program of Federal University of Santa Maria, in the scope of doctorate. From theoretical lines that contemplate studies by Vygotski (1997, 2006, 2007, 2010a), Bakhtin (1988, 2006, 2010), Leontiev (1984), Freire (2000, 2001,2013, 2014, 2015), Tardif (2002), Quadros and Karnopp (1994), Stumpf (2002, 2005), we aimed to comprehend the learning of teaching of the deaf teacher considering the knowledge and practices about the gestuality and writing of sign language, central focus of this study. As specific objectives we seek to identify the trajectories of the deaf teachers about the learning of the writing of sign language; recognize the relation between the gesture sign language proficiency and its writing form in the docent learning, and recognize the knowledge and the practices of the deaf teachers and their implication about the processes of teaching and learning the writing of sign language. For this, the methodological approach used was of qualitative nature and was developed from the sociocultural perspective of narrative content. The data of the research was collected through thirteen meetings of the study group and through semi-structured interviews with five deaf teachers of the school for deaf people of the State Public Education System of the city of Santa Maria - RS. The analysis of narrative gestuality of the deaf teachers, who are responsible for the teaching of the writing of sign language SignWriting, indicated as results the process of learning of their teaching highlighting the constituent elements in this process. The data analysis indicates the category Learning of teaching of deaf teachers that characterizes itself by the form as the teacher organizes the ways of thinking and the practice of teaching, by appropriating the elements that constitute themselves in the practices and knowledge of the profession. This category is divided in three dimensions: the first dimension, conceptions and ideas about the writing of sign language: the knowledge of visual experience, which is expressed by the ideas and conceptions that the deaf teachers manifest about the writing of sign language, emphasizing the knowledge of visual experience, implied in this comprehension. The second dimension named as leaner condition in the context of deafness: the construction of the teaching expresses the way as the teacher learns how to be a teacher in his context, stressing the challenges and conditions of exerting the profession in the school for deaf people. The third dimension teaching practices of deaf teachers: the pedagogical knowledge shared in construction characterizes itself by the moment in which the deaf teachers express their comprehensions about the pedagogical work that they develop focusing on the ways of teaching and learning involved in this process. As results of investigation we noted the investment performed by the deaf teachers in the profession as teachers of writing of sign language. The deaf teachers assume the learning condition facing the reality as possible of transformation. The teaching activity of study instituted among the deaf teachers is a factor that sustains the professional qualification and strength the pedagogical choices, as the adoption of the teaching of writing of the sign language SignWriting. The culture of collaboration instituted in the meetings of the study group favored the re-organization of the practices of deaf teachers strengthening the pedagogical ways adopted. The school for deaf people constitutes itself as a potential space to formation, reflection and innovation of school practices.